2020
DOI: 10.3389/fncel.2019.00571
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cell-Cell Interactions in Parkinson’s Disease Using Human Stem Cell-Based Models

Abstract: Parkinson's disease (PD) is the most frequently occurring movement disorder, with an increasing incidence due to an aging population. For many years, the post-mortem brain was regarded as the gold standard for the analysis of the human pathology of this disease. However, modern stem cell technologies, including the analysis of patient-specific neurons and glial cells, have opened up new avenues for dissecting the pathologic mechanisms of PD. Most data on morphological changes, such as cell death or changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 138 publications
(209 reference statements)
0
7
0
Order By: Relevance
“…The true breakthrough in the generation of mesDA neurons came from the description of the generation of floor plate cells from iPSCs [68], a protocol later applied for differentiation of iPSC into mesDA neurons [69]. In addition to the neuroectodermal induction step mediated by the inhibition of both SMAD main pathways, human mesDA neurons production requires the combined temporal and concentration-dependent activation and/or inhibition of transcription factors and morphogens coming from signaling centers [70]. Among all the protocols that describe the generation of ventral dopaminergic neurons (that are summarized in Table 1), few seemed to recapitulate dopaminergic functions, pointing out the need for new protocols [48,[71][72][73].…”
Section: Producing and Characterizing Ventral Midbrain Dopaminergic Neuronsmentioning
confidence: 99%
“…The true breakthrough in the generation of mesDA neurons came from the description of the generation of floor plate cells from iPSCs [68], a protocol later applied for differentiation of iPSC into mesDA neurons [69]. In addition to the neuroectodermal induction step mediated by the inhibition of both SMAD main pathways, human mesDA neurons production requires the combined temporal and concentration-dependent activation and/or inhibition of transcription factors and morphogens coming from signaling centers [70]. Among all the protocols that describe the generation of ventral dopaminergic neurons (that are summarized in Table 1), few seemed to recapitulate dopaminergic functions, pointing out the need for new protocols [48,[71][72][73].…”
Section: Producing and Characterizing Ventral Midbrain Dopaminergic Neuronsmentioning
confidence: 99%
“…The development of these protocols triggered a wave of characterization studies aiming at identifying altered phenotypes of 2D mDA cultures derived from patient hiPSCs carrying monogenic (PAKR2, PINK1, LRRK2, SNCA, GBA, and OPA1) or sporadic forms of the disease. These phenotypic effects have been well-described in the literature, both at the cellular and molecular levels [see reviews (48)(49)(50)(51)]. To summarize, several converging pathological mechanisms that contribute to the vulnerability of human mDA neurons were reproduced in vitro, including reductions in neuronal arborization, increases in α-syn expression, oxidative stress, and mitochondrial dysfunctions (decreased respiration and ATP production, impaired mitochondrial biogenesis), as well as altered cellular stress responses [such as the unfolded protein and integrated stress responses, which involve the endoplasmic reticulum (52)(53)(54)].…”
Section: Hipsc-derived Models Of Pd In 2dmentioning
confidence: 99%
“…Several studies with hiPSC-derived neurons have revealed dysregulation in the expression of genes involved in numerous cellular processes, rendering cells vulnerable to stressors that activate or modulate these pathways. Oxidative stress, mitochondrial impairment and proteasome inhibition are key factors that cause increased susceptibility and cell death of patient-derived neurons (reviewed in [ 33 , 84 ]). The first study recapitulating PD-associated phenotypes has revealed that dopaminergic neurons derived from LRRK2-G2019S hiPSCs displayed increased expression of key oxidative stress-response genes.…”
Section: Rescue Of Disease-related Phenotypes In Hipsc-derived Modmentioning
confidence: 99%